2005
DOI: 10.4049/jimmunol.175.3.1566
|View full text |Cite
|
Sign up to set email alerts
|

CD25-Expressing CD8+ T Cells Are Potent Memory Cells in Old Age

Abstract: We have recently described an IL-2/IL-4-producing CD8+CD25+ nonregulatory memory T cell population that occurs in a subgroup of healthy elderly persons who characteristically still have a good humoral response after vaccination. The present study addresses this specific T cell subset and investigates its origin, clonal composition, Ag specificity, and replicative history. We demonstrate that CD8+CD25+ memory T cells frequently exhibit a CD4+CD8+ double-positive phenotype. The expression of the CD8 αβ molecule … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
2

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(60 citation statements)
references
References 51 publications
2
56
0
2
Order By: Relevance
“…32 The ability of the CD8 C BTLA C subset to produce more IL-2 could therefore endow them with the preferential ability to expand and persist in vivo after infusion into patients.…”
Section: Discussionmentioning
confidence: 99%
“…32 The ability of the CD8 C BTLA C subset to produce more IL-2 could therefore endow them with the preferential ability to expand and persist in vivo after infusion into patients.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the raw data was performed applying the GeneScan 3.7 analysis software package (Applied Biosystems) using the Local Southern method for fragment size estimation. The frequency of polyclonal, oligoclonal, and monoclonal profiles within the 24 Vb regions from paired BM and PB T cells from five donors was quantified based on deviations from the Gaussian distribution as described previously (14).…”
Section: Intracellular Cytokine Stainingmentioning
confidence: 99%
“…Quantitative RT-PCR experiments were performed using the LightCycler 480 System (Roche Diagnostics), 23 SYBR Green 1 Master (Roche Diagnostics), and GAPDH and b-actin as housekeeping genes for relative quantification of candidate genes as described previously (11). Sequence-specific oligonucleotide primers were designed using Primer3 software (12) TCR Vb CDR3 spectratype analysis TCR Vb transcripts of PBMC and BMMC were amplified by PCR using a HotStarTaq Master Mix Kit (Qiagen) and primers (MWG Biotech) specific for each of the human Vb families and a specific primer for the C region of the b-chain (labeled with fluorescein) as previously described (13,14). An aliquot of the PCR product was diluted in 20 ml formamide and 1.2 fmol internal lane standard GeneScan-500 LIZ (Applied Biosystems).…”
Section: Intracellular Cytokine Stainingmentioning
confidence: 99%
“…As previously mentioned, it has been reported that IL-4 producing T cells with a CD25+ memory phenotype accumulate in a subgroup of healthy elderly people who have an intact humoral immune response after influenza vaccination. These apparently beneficial CD8+ CD25+ T cells are rare or even absent in older persons with latent CMV infection (Herndler-Brandstetter et al, 2005).…”
Section: Chronic Infections and Immune "Exhaustion"?mentioning
confidence: 99%
“…They produce IL-2 and IL-4, assist B memory generation, induce MHC II upregulation on B cells, and promote antibody isotype switching to IgG1 and IgE. These T cells coexpress CD4 molecule and present a highly diverse TCR repertoire and longer telomere compared to the CD8+ CD25-subset (Herndler-Brandstetter et al, 2005).…”
Section: Memory T Cellsmentioning
confidence: 99%